Mapping, tissue distribution and polymorphism of porcine retinol binding protein genes (RBP5 and RBP7) - Gong, W.H.; Tang, Z.L; Yang, S.L.; Wang, H.; Li, Y.; Wang, Z.G.; Li, K.; Han Jianlin (2008)
The retinoids (vitamin A and its derivatives) play a critical role in vision, growth, reproduction, cell differentiation and embryonic development. Using the IMpRH panel, porcine cellular retinol binding protein genes 5 and 7 (RBP5 and RBP7) were assigned to porcine chromosomes 5 and 6, respectively. The complete coding sequences (CDS) of the RBP5 and RBP7 genes were amplified using the reverse transcriptase polymerase chain reaction (RT-PCR) method, and the deduced amino acid sequences of both genes were compared to human corresponding proteins. The mRNA distributions of the two genes in adult Wuzhishan pig tissues (lung, skeletal muscle, spleen, heart, stomach, large intestine, lymph node, small intestine, liver, brain, kidney and fat) were examined. A total of nine single nucleotide polymorphisms (SNPs) were identified in two genes. Three of these SNPs were analyzed using the polymerase chain reaction-restriction-fragment length polymorphism (PCR-RFLP) method in Laiwu, Wuzhishan, Guizhou, Bama, Tongcheng, Yorkshire and Landrace pig breeds. Association analysis of genotypes of these SNP loci with economic traits was done in our experimental populations. Significant associations of different genotypes of [RBP5-A/G.sup.63], RBP5-A/[G.sup.517] and [RPB5-T/C.sup.intron1-90] loci with traits including maximum carcass length (LM), minimum carcass length (LN), marbling score (MS), back fat thickness at shoulder (SBF), meat color score (MCS) and hematocrit (HCT) were detected. These SNPs may be useful as genetic markers in genetic improvement for porcine production.